Integration of agronomical and biological practices for the management of Moniliophthora roreri Cif & Par - Villamil C., Jorge Enrique; Sierra A., Lizeth Johana; Olarte L., Yeimy; Mosquera E., Ana Teresa; Fajardo C., Juan David; Pinzón, Elberth H.; Martínez O., John Wilson (Revista de Ciencias Agrícolas, 2016)
therefore, emerges as an economically viable and environmentally sustainable alternative. The objective of this study was to evaluate Moniliophthora roreri control’s by analyzing incidence and severity parameters, using native and commercial strains of Trichoderma spp., combined with agronomic practices (AP). Ten treatments were evaluated. They included: agronomic practices, biological products, native fungi strains, and chemical fungicide combinations,. A completely randomized design with four replicates and 40 experimental units was used. Each unit consisted of a plant of the TCS01 (Theobroma Corpoica La Suiza 01) variety. Foliage inoculations were done using concentrations of 1.2, 1.5, and 2,9 x107 UFC.g-1 for native fungal strains and 2,0 and 5.0 x108 UFC.g-1 concentrations for commercial strains . External incidence and severity on fruits were evaluated during 25 weeks. Results showed that fruits inoculated with treatment T7 (AP + Safer soil W.P®) and treatment T4 (AP +mixture of Trichoderma H 0, H3, H5) presented the lowest external incidence and severity percentages and the highest yield, without significant differences between the chemical and regional control. According to the results,